The political clan in Calbiga its extent of influence to the voting behavior of the constituents - Cabuello, Clariza D.; Oreo, Cristina D. (1997)
Calbiga, W. Samar is a municipality of the second district of the province, performs certain government function, the election. It is a process of changing local leadership and this usually takes place every three years. In this leadership selection, it is participated by able individuals who will lead the municipalities in such a way that the constituents can avail of the benefits that national government has slated for them.